The Firm-Level Impact of the COVID-19 Pandemic : Summary of Results from Round 3 - World Bank (World Bank, Washington, DC, 2020)
The World Bank commissioned a firm-level survey to provide quantitative evidence of the impact of the Coronavirus 2019 (COVID-19) pandemic. Three rounds of data have been collected in May, July, and August, using a nationally representative World Bank survey providing data on the impact of the COVID-19 pandemic. The survey includes responses from 500 firms spanning a wide range of industries and firm sizes, as well as the formal and informal sector. This note provides a snapshot of how firms’ outcomes and responses to the pandemic have changed throughout the months of May to August.